Clubbing, cyanosis and a new diagnosis of atrial septal defect in a parturient: a straightforward diagnosis of Eisenmenger syndrome?. (17th January 2013) - Butcher, Charles; Plyman, Carla; Hughes, Marina; Walker, Fiona
Abstract : A parturient required emergency admission to intensive care following a major postpartum haemorrhage. She was hypovolaemic, hypoxic and cyanosed and was also noted to have digital clubbing. A transthoracic echo showed a large atrial septal defect (ASD) with right heart dilation and possible anomalous pulmonary venous drainage. Eisenmenger syndrome was diagnosed with cyanosis due to shunt reversal at atrial level (right atrium to left), as a consequence of an elevated pulmonary vascular resistance from chronically increased pulmonary blood flow. After a full initial recovery, she was referred to a specialist grown-up congenital heart disease unit for further investigation. Cardiac MRI confirmed an ASD but showed that the cause of the cyanosis was anatomical in origin. An elongated Eustachian valve was diverting desaturated inferior venacaval blood across the intra-atrial septum into the left atrium. Her congenital heart defect was therefore amenable to corrective surgery.